1984
DOI: 10.1152/jappl.1984.56.3.716
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and metabolic responses to exercise after adrenoceptor blockade in humans

Abstract: The effects of acute alpha 1-adrenoceptor blockade with prazosin, beta 1-adrenoceptor blockade with atenolol, and nonselective beta-adrenoceptor blockade with propranolol were compared in a placebo-controlled crossover study of the hemodynamic and metabolic responses to acute exercise 2 h after prolonged prior exercise to induce skeletal muscle glycogen depletion, enhancing the dependence on hepatic glucose output and circulating free fatty acids (FFA). Plasma catecholamines were higher during exercise after, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Although there was a further increase in Vo^ax between Sessions 3 and 4 that was restricted to the atenolol group, this differential change across groups was not sufficiently pronounced to lead to a significant difference among the groups at Session 4. The present results thus demonstrate that hypertensive subjects resemble normotensive subjects 13 in their ability to achieve benefits in cardiorespiratory fitness, despite the presence of either nonselective or selective /3-blockade. The differences between atenolol and propranolol in their physiological properties 20 did not lead, during long-term administration, to differential effects in the increase in Vo 2 max associated with aerobic exercise training.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Although there was a further increase in Vo^ax between Sessions 3 and 4 that was restricted to the atenolol group, this differential change across groups was not sufficiently pronounced to lead to a significant difference among the groups at Session 4. The present results thus demonstrate that hypertensive subjects resemble normotensive subjects 13 in their ability to achieve benefits in cardiorespiratory fitness, despite the presence of either nonselective or selective /3-blockade. The differences between atenolol and propranolol in their physiological properties 20 did not lead, during long-term administration, to differential effects in the increase in Vo 2 max associated with aerobic exercise training.…”
Section: Discussionsupporting
confidence: 53%
“…/3-Blockade has been found to lead to some deficits during tests of memory (i.e., Wechsler-Russell Memory Scale), 13 and on RT measures of sensory and motor functioning. ' 6i " Miller et al, 18 in contrast, observed that hypertensive subjects improved their performance of cognitive tasks when blood pressure was normalized by pharmacological treatment.…”
Section: -Blockade Exercise and Memory/madden Et Almentioning
confidence: 99%
“…In the present study, neither propranolol nor atenolol modified oxygen consumption or carbon dioxide production. Our previous investigations however have strongly suggested that propranolol but not atenolol impairs hepatic glucose release (McLeod et al, 1983(McLeod et al, , 1984 (Felig & Wahren, 1975). There is evidence for enhanced intramuscular glycogenolysis during exercise after propranolol which would support this concept (Juhlin-Dannfelt et al, 1982).…”
Section: Discussionmentioning
confidence: 95%
“…McLeod et al [6] noted that exercise on healthy human males affected the hemodynamic and metabolic actions of propranolol, atenolol and prazosin.…”
Section: (If Applicable)mentioning
confidence: 99%